Consistent condom use among sexually active hiV-positive women in Amhara region, Ethiopia - Alene KA (Dove Medical Press, 2014)
Kefyalew Addis Alene Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia Background: Consistent condom use has been described as the most effective way to prevent both sexually transmitted infections and HIV transmission among people living with HIV. Therefore, this study assessed the prevalence and factors associated with condom use among sexually active HIV-positive women in Amhara region referral hospitals, Ethiopia. Methods: An institution-based cross-sectional study design was conducted from April to June, 2013 in Amhara region referral hospitals. A standardized questionnaire was used to collect the data. The data were entered into EPI INFO version 3.5.1 statistical software and analyzed by SPSS version 20.0. Binary logistic regression model was used to identify the associated factors. Odds ratios with 95% confidence intervals (CIs) were calculated to assess the strength of association. Results: A total of 351 sexually active HIV-positive women were interviewed. Consistent condom use among sexually active HIV-positive women was found to be 56.7% (51.7%–61.9%). Being in the age groups 30–34 years (adjusted odds ratio [AOR]: 2.82, 95% CI 1.31, 6.08) and 35–39 years (AOR: 2.64, 95% CI 1.15, 6.08), having a relatively large family (three to five family members) (AOR: 2.54 95% CI 1.57, 4.12) and more than five family members (AOR: 1.69 95% CI 0.79, 3.63), and being Muslim or Protestant (AOR: 0.52 95% CI 0.33, 0.84) were variables associated with consistent condom use. Conclusion: Consistent condom use among sexually active HIV-positive women in Amhara region referral hospital was low, suggesting an urgent need for intervention through the involvement of a religious leader. Keywords: condom use, HIV-positive women, Amhara region, Ethiopia